Penerapan Tata Kelola Audit Sistem Informasi Pada Shen Coffee Space Menggunakan Framework COBIT 2019 - Rahmat, Haikal Zaenul; Tukino, Tukino; Nurapriani, Fitria; Huda, Baenil (STMIK Banjarbaru, 2025)
Digital transformation encourages micro, small and medium enterprises (MSMEs) to optimize the use of Information Technology (IT) to support operations and business growth. This research aims to evaluate the maturity level of IT governance at Shen Coffee Space and prepare recommendations for improvements based on the COBIT 2019 framework. The research uses a descriptive method with a survey approach through observation, interviews and questionnaires, which measures five main domains: APO04, APO06, BAI09, DSS01 and DSS03. The analysis results show an average IT maturity level of 3.82 (Defined–Quantitatively Managed) with a GAP of 1.05–1.29 points from the Level 5 (Optimizing) target. This research recommends improvements to innovation systems, IT budgets, asset management, daily operations, and problem management based on root cause analysis. These findings support the effectiveness of implementing COBIT 2019 in improving IT governance in the MSME environmentKeywords: IT Governance; COBIT 2019; MSME; Information System Audit; Maturity Level. AbstrakTransformasi digital mendorong usaha mikro, kecil, dan menengah (UMKM) untuk mengoptimalkan pemanfaatan Teknologi Informasi (TI) dalam mendukung operasional dan pertumbuhan bisnis. Penelitian ini bertujuan mengevaluasi tingkat kematangan tata kelola TI di Shen Coffee Space serta menyusun rekomendasi perbaikan berbasis framework COBIT 2019. Penelitian menggunakan metode deskriptif dengan pendekatan survei melalui observasi, wawancara, dan kuesioner, yang mengukur lima domain utama: APO04, APO06, BAI09, DSS01, dan DSS03. Hasil analisis menunjukkan rata-rata tingkat kematangan TI sebesar 3,82 (Defined–Quantitatively Managed) dengan GAP 1,05–1,29 poin dari target Level 5 (Optimizing). Penelitian ini merekomendasikan perbaikan sistem inovasi, anggaran TI, pengelolaan aset, operasi harian, dan manajemen masalah berbasis root cause analysis. Temuan ini mendukung efektivitas penerapan COBIT 2019 dalam meningkatkan tata kelola TI di lingkungan UMKM.